Awareness and Usage Pattern of Water-Soluble Fertilizer in Himmatnagar Taluka, Gujarat, India - , Asav D. Patel, Chetan R. Dudhagara (Archives of Current Research International, 2025)
Water-soluble fertilizers have become vital in modern agriculture due to their quick absorption and adaptability to crop needs. These fertilizers are especially significant in fruit and vegetable farming, offering enhanced nutrient delivery and improved crop growth. In India, the fertilizer industry has evolved substantially and is now largely self-reliant. The study was conducted to explore the farmers’ awareness and usage pattern of water-soluble fertilizer with 200 samples by using purposive sampling techniques in the himmatnagar taluka of Gujarat. The study revealed that farmers are generally knowledgeable and view these fertilizers as effective and beneficial. Both dealers and farmers emphasized the need for improved pricing, high-quality packaging, and regular product demonstrations. Brand preferences differed depending on performance and availability, with certain brands becoming popular due to their strong market presence. The findings also pointed to experienced and educated farmers being open to adopting new technologies. Overall, the study emphasized the growing role and potential of water-soluble fertilizers in Indian agriculture.